Atomic layer deposition of epitaxial CeO2 thin layers for faster surface hydrogen oxidation and faster bulk ceria reduction/reoxidation. Issue 19 (21st May 2015) - Marizy, Adrien; Roussel, Pascal; Ringuedé, Armelle; Cassir, Michel
<x xml:space="preserve">Abstract</x> Thin ceria layers of 120 nm were processed by atomic layer deposition on both YSZ(100) single crystal substrates and polycrystalline YSZ ones.